PKM. PELATIHAN PENELITIAN TINDAKAN KELAS (PTK) BAGI GURU SEKOLAH TAMAN RAMA DENPASAR (Jurnal Pengabdian Kepada Masyarakat Widya Mahadi, 2021)
Classroom action research is research that can be done by teachers in order to improve the learning process in the classroom to achieve certain goals. This training is to provide solutions to teacher problems that occur in the classes they teach. Community service activities aimed at increasing the understanding of teachers regarding the preparation of CAR proposals in learning at Taman Rama Denpasar schools. Participants in the training activities were teachers from the Taman Rama School in Denpasar. Activities are carried out through training, question and answer and drill through several stages. The methods used in this service activity are (1) Socialization of the preparation of class action research proposals; (2) assistance in writing CAR proposals, (3) Giving assignments to make class action research proposals. In assisting the making of this class action research proposal, each participant is required to make an action research proposal accompanied by a service team from UPMI. Conclusions from the training (1) There is an increase in the skills of teachers at Taman Rama Denpasar School in preparing proposals for classroom action research, (2) In developing academic culture in the Taman Rama Denpasar school environment in improving the quality of education, there has been an increase in making proposals and implementing CAR.